A new large mammal from the Ypresian of Morocco: Evidence of surprising diversity of early proboscideans - (:unkn) unknown (My University, 2002)
We describe a new primitive proboscidean, Daouitherium rebouli gen. et sp. nov., from the early Ypresian of the Ouled Abdoun Basin, Morocco, which also yielded Phosphatherium. It is the earliest known large mammal from Africa and one of the oldest known proboscideans. It has true lophodont molars similar to those of Barytherium and Numidotherium. It is closer to these genera and more advanced than Phosphatherium (e.g., morphology of the mandible), but it is also primi− tive in striking features known also in Phosphatherium (absence of diastema, retention of two additional teeth in front of p2). A parsimony analysis of Daouitherium suggests its intermediate phylogenetic position between the basal, small Phosphatherium and the large, more derived Numidotherium and Barytherium. Daouitherium is a better candidate for the ancestry of N. koholense than Phosphatherium, but it is also specialized. Daouitherium and Numidotherium may belong to the same basal radiation of "Barytherioidea". However, the family referral of Daouitherium is uncertain (Numidotheriidae?). The discovery of such a large and derived proboscidean with respect to Phosphatherium in the same African beds of such antiquity is evidence of an unexpected early diversity of proboscideans and of the old origin of the order. It also supports the African origin of Proboscidea s.s.
Keywords: African Research